(untitled) (Літератури світу: поетика, ментальність і духовність, 2016)
The article analyses the medical discourse of the fiction. The interaction of the medicine, art and literature is examined. The author studies the devoted work of the doctors-writers, analyses their creative work, gives special consideration to the work of the Ukrainian writers that depicted the doctor image in the creative work having a medical degree.